Integration and Synchronization of Population Policies Through Grand Design Population Development in Indonesia (Medico Legal Update, 2020)
The problem of population in Indonesia is complex. Population policy in the era of decentralization is still notintegrated and sustainable. Grand Design of Population Development is a guideline for population-orientedpolicies, strategies and development programs, which contains important current population issues, desiredpopulation conditions, population development programs, population development roadmaps coveringpopulation quantity control, quality development population, family development, spatial planning andpopulation regulation and population administration development. Approach Grand Design of PopulationDevelopment can influencing policy and responsive policy towards population dynamics. With the GrandDesign of Population Development, a region can prepare itself to welcome the demographic bonus that canbe done through improving human quality. Human development as an effort to develop capability the abilityof human self, which contains four elements, namely productivity, equity, sustainability and empowerment.The roadmap set out in Grand Design of Population Development will be implemented on an ongoing basisto improve human quality, reflected in the increasing Human Development Index.